2020
DOI: 10.7759/cureus.6852
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quality and Reliability of YouTube Videos on Rotator Cuff Tears

Abstract: The objective of this study was to investigate quality and scientific accuracy of videos related to rotator cuff tear on YouTube. Methods Term of "rotator cuff tear" was entered to the searching bar of YouTube and the first 50 YouTube videos about rotator cuff tear with the highest view counts were recorded and evaluated by two orthopedists. Title of the videos that met the inclusion criteria were recorded. The videos were evaluated with DISCERN and JAMA scoring system, and Video Power Index. Results The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
94
2
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(123 citation statements)
references
References 25 publications
17
94
2
10
Order By: Relevance
“…In the study conducted by Yurdaisik, it was determined that the videos uploaded by health channels were also of medium quality [ 10 ]. Similarly, in the studies conducted by Kuru et al [ 12 ] and Aydin et al [ 11 ], videos uploaded by health channels were reported to be of medium quality.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In the study conducted by Yurdaisik, it was determined that the videos uploaded by health channels were also of medium quality [ 10 ]. Similarly, in the studies conducted by Kuru et al [ 12 ] and Aydin et al [ 11 ], videos uploaded by health channels were reported to be of medium quality.…”
Section: Discussionmentioning
confidence: 73%
“…We found that only three of the 50 videos we examined were uploaded by patients and all of these contained misleading content. However, it was also reported that videos uploaded by patients were viewed and liked more than videos uploaded by professionals in some previous studies [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Literatürde çeşitli tıbbi konularla ilgili videoların içeriklerinin incelendiği çalışmalarda yüksek kalitede videonun az olduğu belirtilmiştir. [5][6][7][8][9][10][11][12] En sık hasta eğitimi içerikli videoların olduğu görüldü (%58). Video puanlarına bakıldığında astımla ilgili ve diğer sağlık profesyonellerinin videolarının puanlarının diğer kaynaklara göre anlamlı yüksek olduğu gösterildi.…”
Section: Tartişma Ve Sonuçunclassified
“…5 Daha önceki çalışmalarda gastroözefagial reflü, sistemik lupus eritematozus, benign prostat hiperplazisi, Çölyak hastalığı, Human Papilloma virüsü aşısı, eklem hastalıkları, adenotonsillektomi gibi pek çok tıbbi başlık hakkında olan videoların tıbbi bilgi içerikleri değerlendirilmişti. [6][7][8][9][10][11][12] Astımla ilgili çok sayıda video olup, hastalar tarafından bilgi kaynağı olarak kullanılmaktadır ancak literatürde bu videoların içeriklerinin sağlık profesyonelleri tarafından değerlendirildiği sadece bir çalışma mevcuttur. 3 Çalışmamızda ülkemizde de sıklıkla bilgi kaynağı olarak kullanılan Youtube platformunda astımla ilgili Türkçe videoların tıbbi içeriklerini analiz ederek videoların eğitim kalitesini değerlendirmek amaçlanmıştır, bu konuda ülkemizde yapılan ilk çalışma olma özelliğini taşımaktadır.…”
Section: Introductionunclassified